Strategi Harga dan Promosi yang Selaras Maqashid Syariah pada Ritel Halal: Praktik Diskon, Bundling, dan Loyalty Program - samsudin, samsudin (Bayani, 2026)
Halal retail is not only required to sell certified products, but also ensure that pricing and promotion strategies are carried out fairly and transparently so that they are in line with sharia maq??id. This study aims to analyze the practices of discounts, bundling, and loyalty programs in halal retail and assess their suitability with the principles of gharar prevention, property protection, and consumer benefit. The research method used was a qualitative case study through semi-structured interviews with managers and frontline officers, observation of the promotion process at the shelves and cashiers, as well as a review of promotional documents and loyalty program provisions. The results show that discounts are effective in attracting visits, bundling contributes to increased transaction value, and loyalty programs strengthen customer retention. However, a number of risks were found, including inconsistency between labels and systems, unclear conditions, and limited information about unit prices and point validity. As an implementive recommendation, this study offers indicators of promotion governance based on transparency, equity of access, and correction mechanisms. The analytical framework used combines Islamic marketing ethics with Islamic pricing principles to interpret findings and formulate operational improvements that can be audited periodically.